PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN MULTI KURIKULUM DI SEKOLAH DASAR - Dian Wahyuningsih; Fitri Puji Rahmawati; Anik Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore the role of school principals in the development of multi-curriculum in elementary schools. The main focus of this research is to understand how principals design, implement, and evaluate multi-curriculum. Thus, the results of this study are expected to provide a deeper insight into the strategic role of principals in curriculum development and to offer practical recommendations that can be applied to improve the quality of education in elementary schools. This research employs a descriptive qualitative method with a case study approach at Madrasah Ibtidaiyah Muhammadiyah (MIM) Caruban, Madiun City. Data were collected through in-depth interviews, participatory observation, and documentation. The subjects of the study include the principal, teachers, students, and parents. Data analysis was conducted through steps of data reduction, data presentation, and drawing conclusions with verification. The findings reveal that the principal plays a crucial role in the development of multi-curriculum, which includes planning, implementation, and evaluation. The principal collaborates with the teaching team to design an integrative curriculum, facilitates its implementation by providing resources and training, and conducts periodic evaluations to ensure the curriculum's effectiveness. The experience of MIM Caruban shows that visionary leadership and strong collaboration among all school stakeholders are essential for the successful implementation of multi-curriculum.